PROSES REKRUTMEN POLITIK CALON LEGISLATIF LOKAL DI MEDAN PADA PEMILU 2009 - Adela, Fernanda Putra (PERSPEKTIF, 2013)
This research aimed to find out more specifically about the recruitment process of legislative candidates by analyzing the processes and mechanisms conducted by Prosperous Justice Party in the face of legislative elections in 2009 in Medan. This study successfully demonstrated that the quality of PKS candidates are good enough when viewed from the level of education that almost all legislative candidates PKS is a graduate degree and some have passed the postgraduate level. PKS has two times following the general election after changing the name, so that from the experience, candidates for legislative members of PKS has experienced enough, considering that there are also some legislative candidate who was also member of the previous legislature. Personally, the popularity of candidates for legislative members of PKS is not so high, but PKS as an institution has a high popularity in the community. PKS candidates recruitment process is closed, causing the PKS tends to be more exclusive. This is because efforts to preserve the Islamic ideology as the party with the good succession planning, so that the selection of candidates is highly selective made PKS as a form of consistency to the ideology of the party, and regarded as a cadre of people capable of carrying the PKS remain as party da?wah in the political life of the state.